2018
DOI: 10.1155/2018/6793726
|View full text |Cite
|
Sign up to set email alerts
|

Alpha-Tocopherol Serum Levels Are Increased in Caucasian Women with Uterine Fibroids: A Pilot Study

Abstract: Uterine fibroids (UFs) are benign tumors of the reproductive tract, arising from smooth muscle cells of the uterus. Steroid hormones, estrogen, and progesterone are considered to be the most important links in the pathophysiology of UFs. Alpha-tocopherol (AT) is the most active form of vitamin E. What is important as far as UFs are concerned is that ATs contain structural determinants, which makes them possible ligands for estrogen receptors (ERs). We present a retrospective cohort study performed in a univers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
1
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 68 publications
0
22
1
4
Order By: Relevance
“…As for the correlation between vitamin E and UF development, Wise et al (2011) who followed 22,583 premenopausal women [ 34 ] and Martin et al’s (2011) study in 887 women [ 51 ] revealed no significant relationship between vitamin E and UFs. A study by Ciebiera et al (2018) demonstrated a correlation between elevated concentrations of one of the vitamin E vitamers (α-tocopherol) in the blood serum and UF occurrence in Caucasian women, but the study was conducted in a much smaller group than the previous studies [ 146 ]. Therefore, the positive influence of vitamin E could depend on particular gene polymorphisms.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…As for the correlation between vitamin E and UF development, Wise et al (2011) who followed 22,583 premenopausal women [ 34 ] and Martin et al’s (2011) study in 887 women [ 51 ] revealed no significant relationship between vitamin E and UFs. A study by Ciebiera et al (2018) demonstrated a correlation between elevated concentrations of one of the vitamin E vitamers (α-tocopherol) in the blood serum and UF occurrence in Caucasian women, but the study was conducted in a much smaller group than the previous studies [ 146 ]. Therefore, the positive influence of vitamin E could depend on particular gene polymorphisms.…”
Section: Discussionmentioning
confidence: 99%
“…In the pathophysiology of UFs, it is interesting that vitamin E contains structural determinants that make it a possible ligand for estrogen receptors (ERs) [102,156] and it can be described as a specific phytoestrogen [102,146]. A study conducted in postmenopausal women showed that vitamin E reduced the symptoms associated with the lack of estrogens, for ecample, hot flashes or sweating [157].…”
Section: Vitamin E and Uterine Fibroidsmentioning
confidence: 99%
See 3 more Smart Citations